A molecular-scale study on the role of methanesulfinic acid in marine new particle formation. (15th April 2020) - Ning, An; Zhang, Haijie; Zhang, Xiuhui; Li, Zesheng; Zhang, Yunhong; Xu, Yisheng; Ge, Maofa
Abstract: Sulfur species have profound impacts on the formation of secondary organic aerosols in marine regions. As one of the most important organic-sulfur components over the ocean, methanesulfinic acid (MSIA) has received attention. However, its potential role in new particle formation (NPF) is still not fully raveled at the molecular level. Using density functional theory (DFT) combined with the Atmospheric Clusters Dynamic Code (ACDC), the effect of MSIA on the nucleation process of NPF under different atmospheric conditions (varying temperatures and precursor concentrations) has been investigated here. Configuration analysis suggests that MSIA can improve the thermodynamic stability of sulfuric acid (SA) and dimethylamine (DMA)-based clusters via strengthening the proton transfer between SA and DMA. Moreover, the kinetic simulations by ACDC indicate that MSIA can enhance the cluster formation rates of SA-DMA-based clusters, especially at lower temperatures and lower concentrations of SA and DMA. Furthermore, MSIA has been identified to not only promote the growth of small clusters following a catalytic mechanism but also directly participate in the formation of critical clusters according to the traced cluster formation pathways. By analyzing the corresponding branch ratios of growth pathways, the contribution of MSIA to cluster formation increases as the MSIA concentration increases, and decreases with the increasing of DMA concentration. The results indicate that MSIA may be essential to nucleation at regions with insufficient DMA and relatively high concentration of MSIA. This finding may help to reveal some missing sources of marine NPF and to understand the atmospheric organic-sulfur cycle. Graphical abstract: Image 1 Highlights: MSIA can enhance the cluster formation rates of SA-DMA-based clusters especially at lower T and lower [SA] and [DMA]. MSIA can be both a "catalyst" and a "participator" in the growth of clusters. MSIA is essential to NPF at regions with insufficient DMA and relatively more massive MSIA. This study may reveal some missing source of marine NPF.